Skidding dynamic performance of rolling bearing with cage flexibility under accelerating conditions. (March 2021) - Liu, Yuqing; Chen, Zaigang; Tang, Liang; Zhai, Wanming
Highlights: A bearing dynamics model with a lumped-mass flexible cage is established. Cage is compressed in the loaded region while stretched in the unloaded region. Appropriate radial load and acceleration of inner race could attenuate skidding. Increasing connecting stiffness of cage could alleviate the roller skidding. Abstract: Rolling bearings are widely used in rotating machinery and its dynamic performance plays a significant effect on the stability, reliability and even safety of the machine. Presence of the skidding is likely to cause damages to the surfaces of the inner race, the outer race, the rolling elements, and/or the cage. In this paper, a skidding dynamics model of a rolling bearing is established to reveal the skidding characteristics. In the dynamics model, the cage is discretized into several segments having the same number of the rolling elements so as to introduce the flexibility of the cage represented by springs connecting the adjacent segments. And the nonlinear contact forces between the rolling elements and innerraces and the cage, the corresponding friction forces, and the gravity and centrifugal forces of the rolling elements are considered comprehensively. The simulation results are compared with the traditional dynamics model with rigid cage. By using the dynamics model, effects of the radial load, the inner ring acceleration, and the connect stiffness between the mass blocks of the cage on the bearing skidding are investigated. The results indicate that the rolling element skidding generally happens at the time instant that the rolling element is entering or leaving the loaded region. The smaller radial load or the higher angular acceleration of inner ring are the primary causes of the bearing skidding. In addition, increasing the connect stiffness could effectively alleviate the skidding phenomenon. Therefore, the proposed bearing dynamics model is proven to be capable of making a reasonable prediction on the bearing skidding with a more realistic flexible cage.